Clinical characteristics, specific resistance patterns, and molecular mechanisms of carbapenem-resistant Morganella morganii isolates - Zheng, Xiangkuo; Zeng, Weiliang; Liu, Yan; Feng, Luozhu; Zheng, Jiayin; Zhou, Tieli; Qian, Changrui; Zhou, Cui (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectivesThe emergence and spread of carbapenem-resistant Morganella morganii (M. morganii) pose a serious global challenge. This study aimed to investigate the clinical characteristics, resistance patterns, and molecular mechanisms of carbapenem-resistant M. morganii.MethodsA total of 170 M. morganii clinical isolates were collected from the First Affiliated Hospital of Wenzhou Medical University (Wenzhou, China) between January 2016 and December 2017. Carbapenem MICs were determined by antimicrobial susceptibility testing. Carbapenem resistance determinants, including carbapenemase genes (blaKPC-2, blaVIM, blaIMP, blaNDM, and blaOXA-48) and extended-spectrum β-lactamase (ESBL) genes (blaTEM, blaCTX-M-1, and blaSHV), were analyzed by polymerase chain reaction (PCR). PCR and sequencing assays were performed to detect penicillin-binding protein (PBP) mutations. Efflux pump activity was also assessed in carbapenem-resistant isolates. Quantitative real-time PCR (qRT-PCR) was used to determine the relative mRNA expression levels of outer membrane porin-encoding gene ompC and PBP activator-encoding genes lpoA and lpoB.ResultsTwenty-six imipenem-resistant and 108 imipenem-intermediate M. morganii isolates were identified, accounting for 15.29% and 63.53% of cases, respectively. No isolates were resistant to meropenem or ertapenem. Among the 26 carbapenem-resistant isolates, the prevalence of ESBL genes blaTEM and blaCTX-M-1 was 30.77% and 11.54%, respectively, while carbapenemase genes were not detected. Resistant isolates carried more specific PBP mutations than carbapenem-susceptible and carbapenem-intermediate isolates. Efflux pump phenotypes were associated with reduced imipenem susceptibility in 13 carbapenem-resistant isolates. qRT-PCR revealed no significant differences in ompC expression among the resistant, intermediate, and susceptible groups; however, significant differences were observed in lpoA and lpoB expression. Isolates in the imipenem-resistant group carried more PBP mutations.ConclusionM. morganii isolates were commonly non-susceptible to imipenem but remained susceptible to meropenem and ertapenem. Low expression of PBP activator genes (lpoA and lpoB), along with the presence of specific PBP mutations, appeared to be the primary mechanisms of resistance. In addition, efflux pump overexpression may contribute to imipenem resistance in M. morganii.